Healthcare workers as parents: attitudes toward vaccinating their children against pandemic influenza A/H1N1 - Torun Fuat; Torun Sebahat D; Catak Binali (BMC, 2010)
Abstract Background Both the health care workers (HCWs) and children are target groups for pandemic influenza vaccination. The coverage of the target populations is an important determinant for impact of mass vaccination. The objective of this study is to determine the attitudes of HCWs as parents, toward vaccinating their children with pandemic influenza A/H1N1 vaccine. Methods A cross-sectional questionnaire survey was conducted with health care workers (HCWs) in a public hospital during December 2009 in Istanbul. All persons employed in the hospital with or without a health-care occupation are accepted as HCW. The HCWs who are parents of children 6 months to 18 years of age were included in the study. Pearson's chi-square test and logistic regression analysis was applied for the statistical analyses. Results A total of 389 HCWs who were parents of children aged 6 months-18 years participated study. Among all participants 27.0% (n = 105) reported that themselves had been vaccinated against pandemic influenza A/H1N1. Two third (66.1%) of the parents answered that they will not vaccinate their children, 21.1% already vaccinated and 12.9% were still undecided. Concern about side effect was most reported reason among who had been not vaccinated their children and among undecided parents. The second reason for refusing the pandemic vaccine was concerns efficacy of the vaccine. Media was the only source of information about pandemic influenza in nearly one third of HCWs. Agreement with vaccine safety, self receipt of pandemic influenza A/H1N1 vaccine, and trust in Ministry of Health were found to be associated with the positive attitude toward vaccinating their children against pandemic influenza A/H1N1. Conclusions Persuading parents to accept a new vaccine seems not be easy even if they are HCWs. In order to overcome the barriers among HCWs related to pandemic vaccines, determination of their misinformation, attitudes and behaviors regarding the pandemic influenza vaccination is necessary. Efforts for orienting the HCWs to use evidence based scientific sources, rather than the media for information should be considered by the authorities.